Energy Use and Economic Growth in Morocco: A Maximum Entropy Bootstrap Approach - Doha, Atemni; Mohcine, Bakhat (International Journal of Energy Economics and Policy, 2025)
This paper adds to the literature in the energy use-economic growth nexus, by analysing the relationship between GDP (Gross Domestic Product) per capita and energy consumption (EC) per capita in Morocco, following a bivariate framework using the Maximum Entropy Bootstrap (MEB) method, on a 1971-2021 time series. This method is particularly advantageous for the statistical analysis of non-stationary time series, eliminating the need for transformation to achieve stationarity, which proves to be problematic for evolutionary time series that change over time, hence affecting the results. The MEB gives more robust results even in the case of small samples. Our results are separated between the first six static models, which have demonstrated bidirectional causality, while the other six dynamic models showed different results, depending on the time-period, however most of them support the neutrality hypothesis. The results we obtained are reliable given the robustness of the MEB method. We suggest more studies to consider utilizing this method in this nexus considering multivariate framework.